Attributes of the figure in the work of Afifa Aleiby (Al-Academy, 2022)
The experiments and artistic performances in contemporary Iraqi painting varied between objective simulation and experimentation in other invisible worlds through metaphor and employment to express the latent implications between the human relationship with the tangible and the intangible. The research problem contained the answer to the following questions to understand the formal features in Afifa Laibi's drawings: What are the formal features of Afifa Laibi's drawings and what are the intellectual transformations that she embodied in presenting her subjective subjects? Did the Iraqi and global environmental changes and influences contribute to the forms of Afifa Laibi? The importance of the research also lies in the study of one of the experiences of Iraqi artists in the means and objectives. The aim of the study was to identify the characteristics of the figure in the drawings of Afifa Laibi. After that, the second chapter of the theoretical framework included two sections: the first (form features) and the second, Afifa Laibi (experience and style) with indicators As for the third chapter, the research procedures, which included how to choose a research community and analyze sampling samples, and then the most important results